Peran Supervisi Kepala Madrasah dalam Meningkatkan Mutu Pendidikan di MTs Negeri Kulon Progo - Legiman (Pusat Pengembangan Madrasah (PPM), dan Fakultas Ilmu Tarbiyah dan Keguruan UIN Sunan Kalijaga Yogyakarta, 2019)
This research aims to determine the role of the head of Madrasah in improving the quality of education in MTs Negeri 4 Kulon Progo, and to help improve the competency of teachers in the learning activities with a real, measurable, controlled, directional program to achieve learning objectives. This research uses qualitative descriptive methods with data collection through observation, interviews and documentation. The results of this research are: 1) supervision of the head of the district of the state of the principal of the school 4 Kulon Progo includes education, managerial, administrator, supervisor, leader, innovator, and motivator; 2) The role of quality improvement is done by increasing the professionalism of teachers by giving opportunities to teachers; 3) Factors affecting the implementation of the head of the Madrasah include: the planning, implementation and follow-up that is carried out continuously to the teachers and education personnel.